Struktur dan Fungsi Pantun Tradisi “Palang Pintu” Sanggar Bang Bens di Rawa Belong Jakarta Barat - Muhamad Dwi Juniarto (Stilistika : Journal of Indonesian Language and Literature, 2021)
This article is about Sturucture and Function of Pantun at Betawi tribe in Rawa Belong West Jakarta. The choice of this topic departs from the author's interest in the form and structure of Betawi rhymes. The formulation of the problem is focused on two things. First, the structure of the Betawi rhyme and the social functions of the rhyme for the Betawi people. The theory used is the theory of structural strata norm of Roman Ingarden and the theory of function of Alan Dundes and William R. Bascom. The method used is to listen and record with the technique of Listening Free Libat Cakap. Analysis of Betawi rhymes shows variations in structure that are different from conventional rhymes and rhymes from other regions. Layers of sound Assonance or repetition of vowels dominated by vowel e {?}, Alliteration or repetition of consonant sounds dominated by ng {?}, rhyme dominated by {er-er} continuous rhyme and cross rhyme {an-i-an}. Euphemism, sarcasm and hyperbole in rhymes are found and dominate. The function as a means of coercion and supervisor of norms in society is very thick in Betawi rhymes. The discovery of the intensity of the entertainment function in words that form distinctive stanzas and rhymes